Learning Analytics: a bibliometric analysis of the literature over the last decade - Ana Azevedo (Elsevier, 2021)
Learning Analytics is a recent and dynamic area of research. It is important, after a decade of the first published article in the area, to get insights about it. This article presents a bibliometric study conducted in order to better know their main aspects. Data was collected from the Web of Science Core Collection. The analysis of the data was two-folded. On the one side, a descriptive analysis was performed using several bibliometric measures, namely, number of articles published by year, number of publications by year, number of citations by publication's age, countries of the publications, institutions of the publications, languages used, number of authors per publication, most productive authors, most cited authors. On the other side a co-authorship analysis was made considering authors, countries, and institutions as unit of analysis. The results obtained allowed to identify the evolution of the area, the main players in the area, namely authors, countries, and institutions. This article contributes to a deeper knowledge of the area of research Learning Analytics helping future researchers start their research in this area.